Pyridine nucleotide regulation of the KATP channel Kir6.2/SUR1 expressed in Xenopus oocytes. - Dabrowski, M; Trapp, S; Ashcroft, F (2003)
The pancreatic beta-cell type of ATP-sensitive potassium (KATP) channel (Kir6.2/SUR1) is inhibited by intracellular ATP and ADP, which bind to the Kir6.2 subunit, and is activated by Mg-nucleotide interaction with the regulatory sulphonylurea receptor subunits (SUR1). The nicotinamide adenine dinucleotides NAD and NADP consist of an ADP molecule with a ribose group and a nicotinamide moiety attached to the terminal phosphate. Both these molecules block native KATP channels in pancreatic beta-cells at concentrations above 500 microM, and activate them at lower concentrations. We therefore investigated whether NAD and NADP interact with both Kir6.2 and SUR1 subunits of the KATP channel by comparing the potency of these agents on recombinant Kir6.2DeltaC and Kir6.2/SUR1 channels expressed in Xenopus oocytes. Our results show that, at physiological concentrations, NAD and NADP interact with the nucleotide inhibitory site of Kir6.2 to inhibit Kir6.2/SUR1 currents. They may therefore contribute to the resting level of channel inhibition in the intact cell. Importantly, our data also reveal that this interaction is dependent on the presence of SUR1, which may act by increasing the width of the nucleotide-binding pocket of Kir6.2.